Fabrication, characterization and electrochemical performance of single strand carbon fiber prepared by catalytic chemical vapor decomposition method - Joshi, Vrushali S.; Gokhale, Suresh P.; Patil, Kashinath R.; Haram, Santosh K. (Electrochimica Acta, 2010)
Preparation, fabrication and voltammetric characterizations of a single strand of carbon fiber (SSCF) electrode and their potential applications for biosensor are presented. SSCFs of diameter ca. 10 +/- 2 mu m and few millimeters in length are prepared by catalytic chemical vapor decomposition (CCVD) method. Voltammetry with potassium ferricyanide. alpha-methylferrocene methanol and hexaammineruthenium(III) chloride on SSCF electrode are used as bench marks to validate the electrode properties. Quasi-steady state voltammograms obtained were fitted into a cylindrical diffusion model From which, the standard rate constant (k(0)) and electron transfer coefficient (alpha) are obtained. The use of SSCF electrode is demonstrated for the voltammetric detection of the micromolar quantity of dopamine in the presence of large excess (ca. 200 times) of ascorbic acid, without any fouling of electrode surface. The kinetics of electron transfer are investigated. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: alpha-Methylferrocene methanol; Ascorbic acid; Catalytic chemical vapor decomposition (CCVD); Cylindrical diffusion; dopamine; Hexaammineruthenium(III) chloride; Single strand carbon fiber (SSCF) electrode

Facile room temperature synthesis of ZnO nanoflower thin films grown at a solid-liquid interface - Jadhav, Aarti H.; Patil, Sagar H.; Sathaye, Shivaram D.; Patil, Kashinath R. (Journal of Materials Science, 2014)
Hierarchical ZnO films consisting of nanoflower particulates are successfully grown by a solid-liquid interface reaction technique at room temperature without additives like surfactants, capping agent, or complexing agent. The structural, morphological, and photocatalytic properties of these films are studied using scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and UV-Vis spectroscopy. The nucleation, growth processes and hence the resulting morphology of the end product can be regulated by changing the concentration of LiOH and the time of reaction. SEM throws light on the chronology of the flower formation by studying the intermediate morphology. Electron microscopy results indicated that these ZnO nanostructures self-assembled to produce flower-like nanostructures. The highest photocatalytic efficiency was observed for the films prepared at the concentration of LiOH 0.5 mg/mL in ethanol at 24 h. On the basis of the results, a plausible growth mechanism for the formation of flower-like ZnO nanostructures is discussed.